2018
DOI: 10.1002/jcb.28065
|View full text |Cite
|
Sign up to set email alerts
|

KDM4B promotes gastric cancer metastasis by regulating miR‐125b‐mediated activation of Wnt signaling

Abstract: Emerging evidence has demonstrated that the aberrant expression of histone‐modifying enzymes such as histone demethylases contributes to gastric carcinogenesis and progression. The role of KDM4B in cancer progression has been gradually revealed. However, the underlying mechanisms regulating gastric cancer metastasis of KDM4B remain unclear. In the present study we determined KDM4B expression in gastric cancer and its biologic function in vitro and in vivo. We found that KDM4B expression was significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…During recent years, researchers have explored the potential mechanism by which miRNA-125b (precursor of miRNA-125b-5p) is involved in gastric cancer. One other previous research showed that miR-125b was as an intermediary between KDM4B (a histone-modifying enzyme) and Wnt signaling [ 18 ]. Another demonstrated that miR-125b targeted the PPP1CA-Rb signal pathway to enhance the migration and invasion of gastric carcinoma cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, researchers have explored the potential mechanism by which miRNA-125b (precursor of miRNA-125b-5p) is involved in gastric cancer. One other previous research showed that miR-125b was as an intermediary between KDM4B (a histone-modifying enzyme) and Wnt signaling [ 18 ]. Another demonstrated that miR-125b targeted the PPP1CA-Rb signal pathway to enhance the migration and invasion of gastric carcinoma cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the Wnt/β-catenin signaling pathway is of great importance in regulating tumor cell growth and metastasis (27,28), and inactivation of Wnt/β-catenin signaling suppresses the growth and progression of numerous cancers, including NSCLC (29). Increasing evidence has revealed that active Wnt/β-catenin signaling can lead to T-cell exclusion and resistance to anti-PD-L1/anti-CTLA-4 monoclonal antibody therapy in melanoma (16).…”
Section: Discussionmentioning
confidence: 99%
“…KDM4B binds to the promoter of β‐catenin target genes and increase its transcription via H3K9 demethylation. KDM4B also upregulates miR‐125b expression and activates the Wnt signaling pathway . After Helicobacter pylori infection, KDM4B induced by the β‐catenin pathway along with nuclear factor‐κB (NF‐κB) binds to the cyclooxygenase‐2 (COX‐2) promoter to COX2 transcription .…”
Section: Altered Expression and Functions Of Kdm4s In Cancermentioning
confidence: 99%
“…80,100 KDM4B knockdown markedly suppresses tumor proliferation and xenograft tumor growth in vivo, 80 while KDM4B inhibition by targeted siRNA or miR-491-5p reduces the migration and invasion of gastric cancer cells in vitro 100 and metastasis in vivo. 101,102 In addition, inhibition of KDM4B prevents the EMT of gastric cancer cells, whereas ectopic overexpression of KDM4B induces EMT. The expression level of KDM4B is also positively correlated with TNM stage, tumor differentiation status, tumor size, tumor invasion, lymph node metastasis, and distant metastasis in gastric cancer patients KDM4B expression is induced via the β-catenin signaling pathway and contributes to the regulation of other downstream target genes through physical association with β-catenin.…”
Section: Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation